EFFECTS OF DRAINAGE DITCHES ON WATER TABLE LEVEL, SOIL CONDITIONS AND TREE GROWTH OF DEGRADED PEATLAND FORESTS IN WEST KALIMANTAN - Astiani, Dwi; Burhanuddin, Burhanuddin; Curran, Lisa M.; Mujiman, Mujiman; Salim, Ruspita (Indonesian Journal of Forestry Research, 2017)
Currently, tropical peatland forests are under considerable pressure because of increasing deforestation and degradation of forests. In Kalimantan, degradation and deforestation of peatland forests are driven primarily by industrial logging, expansion of agricultural activities through primarily conversion of forests to agricultural land and oil palm plantations. By the establishment of intensive drainage, it can induce wildfires in peatland. Unmanaged drainage ditches will alter water table levels within the site adjacent to the drainage including to surrounding peatland forest. Water table assessments were conducted before and after peatland drainage on 2007/2009 and 2012/2015 in Kubu Raya, West Kalimantan. This paper studies the effect of drainage ditches into the peatland water table. Results show the establishment of drainage ditches on this peatland landscape lowered the water table by more than 3 times from ~11.7 cm (SE = 1.5, n = 5) to ~37.3 cm (SE = 2.1 cm, n = 26). The effect on the water table was in drier months of July-August. Lowering the water table level altered worst the soil micro climate, peat temperature and peat water content. The results indicate the land use changes in peatland with the establishment of drainage affects peatland water table currently. In the area of less than 500 m from the drainage, the water level tends to lower toward the drainage feature. Therefore, recovery of peatland forests should be initiated by managing the landscape hydrology (i.e. water table) to restore the ecosystem and to protect the remaining peat swamp forest.